Voltage stability improvement and transmission loss minimization for a 5-Bus Oman system based on modal analysis and reactive power compensation - AL Mamari, Adnan Saidf Said; Toha, Siti Fauziah (International Journal of Innovative Science and Research Technology i, 2019)
The aim of this paper is to proposed a method to analyze and improve a technique to find out the ideal amount of reactive power as a compensation in order to reduce the power loss in electrical system and as well to develop voltage magnitude profiles. The first step is to calculate the required amount of reactive power and then it is injected to each load bus. Additional analysis is implemented in order to inject that amount of reactive power into certain buses. The proposed algorithm is implemented in Matlab for 5- Bus Oman selected grid and the obtained results are closed to that data which provided by Oman Electricity Transmission Company which helped to verified.